"Training and the New Industrial Relations": New Zealand Research that Explores Streeck’s Thesis - Michael Law; Piercy Gemma (Adult Education Research Conference, 2000)
This New Zealand research finds some support for Wolfgang Streeck’s thesis that education and training offer unions strategic possibilities in a neo-liberal environment. But it also finds that political strategies are necessary when unions’ quasi-constitutional status has been substantially diminished.